Fabrications : New and Selected Stories - Painter, Pamela (Book collections on Project MUSE., 2020)
"This is a collection of new and previously published short stories by a three-time Pushcart Prize-winning author of fiction. The author's stories have been cited for their wicked intelligence and ruthless humor as her characters celebrate their addictions and appetites"--